(untitled) (Journal of Scientific Research, 2018)
The fluctuations in the Interplanetary Magnetic Field significantly affect the state of geomagnetic field particularly during the Coronal Mass Ejection (CME) events. In the present investigation we have studied the influence of Interplanetary Magnetic Field changes on the geomagnetic field components at high, low and mid latitudes. To carry out this investigation we have selected three stations viz. Alibag (18.6°N, 72.7°E), Beijing MT (40.3°N, 116.2°E) and Casey (66.2°S, 110.5°E) one each in the low, mid and high latitude regions. Then we selected geomagnetic storm events of three types namely weak (-50≤Dst≤-20), moderate (100≤Dst≤-50) and intense (Dst≤-100nT). In each storm category 10 events were considered. From our study we conclude that geomagnetic field components are significantly affected by the changes in the IMF at all the three latitudinal regions during all the storm events. At the same time we also found that the magnitude of change in geomagnetic field components is highest at the high latitudes during all types of storm events while at low and mid latitude stations the magnitude of effect is approximately the same.